2017
DOI: 10.3892/etm.2017.4655
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-19a promotes nasopharyngeal carcinoma by targeting transforming growth factor β receptor 2

Abstract: MicroRNA (miR), a class of small non-coding RNA, function as key regulators in gene expression through directly binding to the 3′ untranslated region of their target mRNA, which further leads to translational repression or mRNA degradation. miR-19a, a member of miR-17-92 cluster, has an oncogenic role in a variety of malignant tumors. However, the exact role of miR-19a in nasopharyngeal carcinoma (NPC) has not previously been studied. The present study aimed to investigate the function and mechanism of miR-19a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Drawn from a previous study, it is concluded that miR-18a is overexpressed in NPC tissues with its association with lymph node metastasis and clinical stage [5]. Besides that, miR-17-92 cluster members including miR-18a are documented to be overexpressed in NPC tissues [25]. Furthermore, upregulated miR-18a is reported to demonstrate in NPC tissues which is connected with tumor node metastasis stage and tumor size [4].…”
Section: Discussionmentioning
confidence: 98%
“…Drawn from a previous study, it is concluded that miR-18a is overexpressed in NPC tissues with its association with lymph node metastasis and clinical stage [5]. Besides that, miR-17-92 cluster members including miR-18a are documented to be overexpressed in NPC tissues [25]. Furthermore, upregulated miR-18a is reported to demonstrate in NPC tissues which is connected with tumor node metastasis stage and tumor size [4].…”
Section: Discussionmentioning
confidence: 98%
“…Many studies have demonstrated that miRNAs take part in the regulation of NPC progression. miR-19a was found to be upregulated and promote development of NPC via targeting TGFβR2 [23]. Similarly, upregulation of miR-192 was also found in esophageal squamous cell carcinoma and squamous cell lung carcinoma [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that TGFR-2 expression has been suggested as a positive prognostic marker in DLBCL patients [ 105 ]. Further, the mRNA and/or protein levels of TGFBR1 and TGFBR2 were found to be significantly reduced in primary NPC tissues compared with non-cancerous controls, and their decreased expression correlated with poor survival [ 106 , 107 , 108 , 109 ]. However, a recent report described contradictory results in which TGFR-1 was found to be up-regulated in primary NPC tissues [ 110 ].…”
Section: Resistance Of Ebv-positive Cells To Tgf-β-mediated Cytostmentioning
confidence: 99%
“…The involvement of cellular miRNAs in the disruption of TGF-β signalling has also been reported. For example, miR-93 and miR-19a, paralogues of the oncogenic miR-17-92 cluster, were shown to promote NPC aggressiveness by down-regulating TGFR-2 [ 108 , 109 ]. Several studies on global miRNA profiling in NPC have identified a number of differentially expressed miRNAs that target the TGF-β pathway [ 114 , 115 , 116 ], but the exact targets within the pathway are yet to be identified.…”
Section: Resistance Of Ebv-positive Cells To Tgf-β-mediated Cytostmentioning
confidence: 99%